A Hybrid Framework for The Implementation of Business Intelligence Systems in Small Scale Enterprises - Chikohora, Teressa Tjwakinna; Esiefarienrhe, Bukohwo Michael (Journal of Information Systems and Informatics, 2022)
Small scale enterprises can improve their operations by implementing business intelligence systems. The business intelligence systems are complex and require expertise to ensure successful implementation, hence the need for small scale enterprises to determine their readiness before undertaking the project. To improve chances for successful implementation, this study proposed a framework to guide small scale enterprises on the requirements for business intelligence systems. The design steps defined by Edwards and Goodrich & Tamassia were followed to design the framework. The framework components were informed by the Diffusion of Innovation and Technology Organization and Environment theories, the Information Evaluation Model, and the critical success factors for BIS implementation. A small business may evaluate its resources against the framework components to determine whether to implement a business intelligence system. In future, the framework may be extended to include weights and other criteria to calculate a business’s status.
Keywords: business intelligence, implementation framework, small scale enterprise, business intelligence system